Sinkronisasi File Pada Google Drive Berdasarkan Perbandingan File Modification Date - Limantoro, Kevin Darmawan; Andjarwirawan, Justinus; Noertjahyana, Agustinus (Jurnal Infra, 2013)
Online storage such Google Drive is created to answer current lifestyle of people all over the world. Nowadays, most people use more than one device, especially for those who lived on advance country. Using online storage, not only their data is safe but also can be accessed anytime online. The thing is most of these people want to have the latest version from a file in all their device. To always keep and update the latest version of file, these people can use synchronization.Because of that, this application is able to do two way file synchronization which is from android device to Google Drive and also otherwise from Google Drive into the android device is made on this final assignment. The method I will use is date comparation, so file with latest modification date will be duplicated to replace the older file. With this method both storage will always have the latest updated file. All synchronization and other processes like compare, upload, download, share, and update will be use based on function Google Drive API. Application will be made using Java version of Eclipse IDE combined with Android Development Tool, because this application will run on android platform devices.